(untitled) (MAUSAM, 1955)
Recent determinations of the nitrates and ammonia in rain water in Sweden has led to the conclusion that thunder, i.e., electrical spark discharges in the atmosphere, is not the determining factor in the production of Nitrogen compounds formed in rain water. In the light of the above conclusion, available data of combined Nitrogen in rain water in India have been examined. It supports the conclusions reached by Swedish workers.